Anticoagulation‐refractory strokes and selective infarction pattern: What's the link?. Issue 1 (8th December 2020) - Dimancea, Alexandru; Ene, Amalia; Badea, Raluca; Ribigan, Athena
Abstract: Stroke etiology in the form of a CAP should be actively explored, especially in the context of previous negative work‐up and anticoagulant‐refractory strokes. Dual antiplatelet therapy proved superior to anticoagulation for secondary prevention. Abstract : Stroke etiology in the form of a CAP should be actively explored, especially in the context of previous negative work‐up and anticoagulant‐refractory strokes. Dual antiplatelet therapy proved superior to anticoagulation for secondary prevention.